The effect of hydraulic conditions on the performance of an upflow anaerobic filter at ambient temperatures treating synthetic winery wastewater - Fleming, Warren Francis (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.